Costs and Benefits of Requiring an Engagement Partner Signature: Recent Experience in the United Kingdom - Carcello, Joseph V.; Li, Chan (The Accounting Review, 2013)
ABSTRACT: This paper investigates the effects on audit quality and audit fees of requiring the engagement partner to sign the audit report in the United Kingdom (U.K.). The effect of requiring the engagement partner to sign the audit report is timely since the Public Company Accounting Oversight Board (PCAOB) is considering mandating a similar requirement in the United States (U.S.). In the first year after the introduction of the signature requirement, we find a significant decline in abnormal accruals and the propensity to meet an earnings threshold, and we find a significant increase in the incidence of qualified audit reports and in earnings informativeness. In addition, audit fees are significantly higher in the post-signature period than in the pre-signature period. Moreover, we compare U.K. firms with a matched sample of U.S. firms and firms in other European countries in periods both before and after the U.K. adopted a signature requirement. Our results are generally consistent with the argument of improved audit quality in U.K. firms after the signature requirement is adopted. Data Availability: Data are available from public sources identified in the text.